Disparity Of Court Decisions In The Authority To Adjudicate Shari'ah Economic Disputes - Zainal Arifin*; Suparnyo Suparnyo (Universitas Syiah Kuala, 2023)
The State of Indonesia is a state based on law and not based on power. Law must be made commander in chief in carrying out the wheels of national and state life.Method approach used _in study This is doctrinal approach. Study This make secondary data as source mainly. Secondary data collection done with study library, that is with learn regulations, documents nor books and _ doctrine or opinion of scholars. Data processing is done through the editing process for correcting erroneous data, adding missing data and complete missing data complete. Results studies show that happening decision disparity about authority judge case economy proposed Shari'ah by Institution Protection Consumers (LPKSM) between judges on religious courts and court country caused exists difference view to authority judge case economy proposed Shari'ah by Institution Protection Consumers (LPKSM). Difference decision between religious court judges and court country about authority judge case the caused by difference interpretation.